Classifying Alumni Satisfaction in Integrity Zone Universities Using CART: Evidence from Indonesian Higher Education - Nurhasanah Nurhasanah; Eka Baqtini; Evi Ramadhani; Nany Salwa; Latifah Rahayu Siregar (UIN Sumatera Utara, 2025)
This study examines alumni satisfaction within the Integrity Zone framework in Indonesian higher education using survey data collected from 315 alumni out of a total population of 1,483 graduates. Alumni satisfaction was dichotomized into satisfied and dissatisfied groups and analyzed using the Classification and Regression Tree (CART) method to identify the most influential service related factors. The results indicate that employee sincerity, service timeliness, completeness of information, adequacy of facilities, and institutional transparency particularly the availability of anti-corruption information are the key determinants of alumni satisfaction. The CART model achieved an Area Under the Curve (AUC) value of 0.73, indicating fair discriminative ability according to standard classification guidelines. These findings provide practical insights for improving service quality and integrity-oriented governance in higher education institutions.